PENERAPAN METODE LATIHAN UNTUK MENINGKATKAN KEMAMPUAN GURU BAHASA INDONESIA MEMANFAATKAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR DI SDN 003 ROKAN IV KOTO - M. Yanis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Based on the observations, teachers were found to rarely utilize the school environment as a learning resource. The school environment was generally used only as a place for students to play during recess. Outside recess time, teachers often chose to keep students confined to the classroom, even though many students appeared bored and saturated with classroom learning. This study employed school action research with 17 teachers as the research subjects. Based on the analysis and discussion of data from the first and second cycles, it can be concluded that the ability of Indonesian language teachers to utilize the school environment as a learning resource improved through a training-based approach. This improvement was evidenced by the results of each cycle. In the first cycle, 11 teachers (64.7%) were categorized as having sufficient ability, while 6 teachers (35.3%) were categorized as having low ability. In the second cycle, teachers’ abilities showed significant improvement, with 14 teachers (82.4%) categorized as good and the remaining 3 teachers (17.6%) categorized as sufficient. These findings indicate that training effectively enhanced teachers’ competence in using the school environment as a learning resource.